Mitochondrial and liver oxidative stress alterations induced by N‐butyl‐N‐(4‐hydroxybutyl)nitrosamine: relevance for hepatotoxicity. Issue 6 (16th November 2011) - Oliveira, Maria M.; Teixeira, José C.; Vasconcelos‐Nóbrega, Cármen; Felix, Luis M.; Sardão, Vilma A.; Colaço, Aura A.; Oliveira, Paula A.; Peixoto, Francisco P.
ABSTRACT: The most significant toxicological effect of nitrosamines like N ‐butyl‐ N ‐(4‐hydroxybutyl)nitrosamine (BBN) is their carcinogenic activity, which may result from exposure to a single large dose or from chronic exposure to relatively small doses. However, its effects on mitochondrial liver bioenergetics were never investigated. Liver is the principal organ responsible for BBN metabolic activation, and mitochondria have a central function in cellular energy production, participating in multiple metabolic pathways. Therefore any negative effect on mitochondrial function may affect cell viability. In the present work, ICR male mice were given 0.05% of BBN in drinking water for a period of 12 weeks and were sacrificed one week later. Mitochondrial physiology was characterized in BBN‐ and control‐treated mice. Transmembrane electric potential developed by mitochondria was significantly affected when pyruvate–malate was used, with an increase in state 4 respiration observed for pyruvate–malate (46%) and succinate (38%). A decrease in the contents of one subunit of mitochondrial complex I and in one subunit of mitochondrial complex IV was also observed. In addition, the activity of both complexes I and II was also decreased by BBN treatment. The treatment with BBN increases the susceptibility of liver mitochondria to the opening of the mitochondrial permeability transition pore. This susceptibility could be related with the increase in the production of H2 O2 by mitochondria and increased oxidative stress confirmed by augmented susceptibility to lipid peroxidation. These results lead to the conclusion that hepatic mitochondria are one primary target for BBN toxic action during liver metabolism. Copyright © 2011 John Wiley & Sons, Ltd.